The CARIFORUM-EC Economic Partnership Agreement : a tool for stimulating innovation in Barbados (Barbados. Ministry of Foreign Affairs and Foreign Trade. Foreign Trade Division. EPA Implementation Unit BellevilleBB, 2010)
Provides industry stakeholders and member of the public with concise and key provisions of the Econonic Partnership Agreement.
Keywords: PARTNERSHIP